Comparison of anatomical tibial plateau angle versus observer measurement from lateral radiographs in dogs - Grierson, J.; Sanders, M.; Guitan, J.; Pead, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
This study was conducted to compare the anatomical tibial plateau angle (TPA) with that measured by observers from a lateral radiograph of the limb, the hypothesis being that there would not be any statistically significant differences between the observer measured TPA and the true anatomical TPA. Twelve pelvic limbs from skeletally mature greyhound cadavers, without any clinical or radiographic evidence of stifle pathology, were used in this study. The radiographs were taken of each limb in a lateral position with the primary beam centered over the tibial eminences and collimated to include the stifle and tarso-crural joints. For subsequent radiographs, Kirschner wires were inserted to enable identification of the tibial plateau. The TPA was then measured, by three observers, from the plain radiographs and by one observer from the marked radiographs. The mean observer TPA was 24.4° (range 17–30°) and the mean anatomical TPA was 23.8° (range 15–31°). The mean and median discrepancy between the anatomical TPA and the observer TPA was negative and very small (− 0.64° and 0°). The magnitude of the discrepancy between individual measurements made by the observers tended to overestimate small angles and underestimate the large ones, and this trend is statistically significant. These results suggest that the measurements made by observers accurately represent the anatomical slope of the tibial plateau. Therefore, observer TPA is suitable for the planning and assessment of TPLO procedures. However, as the anatomical TPA moves away from a median angle (23.25°) the magnitude of error in the measurement increases.
Keywords: Tibial plateau angle; dog; anatomical